2021
DOI: 10.1111/aos.14999
|View full text |Cite
|
Sign up to set email alerts
|

Interrater reliability and agreement between children with visual impairment and their parents on participation and quality of life

Abstract: Purpose To investigate interrater reliability and agreement between children with visual impairment (VI) and their parents on participation and quality of life and factors associated with disagreement. Methods Children 7–17 years and their parents completed the PAI‐CY 7–12 (n = 180) and 13–17 (n = 65), the KIDSCREEN‐27 (n = 250) and the CASP (n = 70). Mean scores of children and parents were compared, with effect sizes for the differences. Interrater reliability was evaluated using intraclass correlation coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…A study in small children showed that weaker parent–child relationships and better social support of children were associated with more discrepancies [ 28 ]. Comorbidities have also been found to be factors associated with discrepancies in visually impaired children [ 29 ]. Moreover, the level and type of education of the children and the level of education of the parents were also found to be significantly associated with discrepancies, as was the number of hospital admissions for children with chronic diseases [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study in small children showed that weaker parent–child relationships and better social support of children were associated with more discrepancies [ 28 ]. Comorbidities have also been found to be factors associated with discrepancies in visually impaired children [ 29 ]. Moreover, the level and type of education of the children and the level of education of the parents were also found to be significantly associated with discrepancies, as was the number of hospital admissions for children with chronic diseases [ 30 ].…”
Section: Introductionmentioning
confidence: 99%